A re-description of Accalathura crenulata (Richardson, 1901) from type material and the description of two new Accalathura species (Crustacea: Isopoda: Cymothoida) - King, Rachael A. (Zootaxa, 2008)
Two new species of leptanthurid isopods in the genus Accalathura are described: A. schotteae, from collections off Panama and A. kensleyi from Belize (material previously identified as A. crenulata in the collections of the National Museum of Natural History, Washington D.C.). The type species of the genus, Calathura crenulata Richardson, 1901, is redescribed from type material and a key to the species of Accalathura in the Caribbean and an adjacent region is given.